Defeating variability in cloud applications by multi-tier workload redundancy (2016)
Workload redundancy emerges as an effective method to guarantee quality of service (QoS) targets, especially tail latency, in environments with strong capacity variability such as clouds. Nevertheless mostly single-tier replication strategies have been studied, while multi-tier architectures are a very popular choice in cloud deployed applications. In this poster we raise the awareness on the challenges of devising a multi-tier replication strategy and its possible benefits through a 2.3X tail latency improvement on an exemplary real-world application.